2009
DOI: 10.1002/jbm.a.32561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioactive glass crystallization on the conformation and bioactivity of adsorbed proteins

Abstract: Protein adsorption onto the surface of a biomaterial mediates cell adhesion and enhances tissue-implant integration. In a previous study, we demonstrated that crystallization of bioactive glass (BG) significantly increased the negative zeta potential and decreased serum protein adsorption onto the material surface. In this study, the conformation of protein adsorbed onto the surface of amorphous bioactive glass (ABG) and crystallized bioactive glass (CBG) was analyzed and correlated to bone marrow mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…The ATR–FTIR bands in the spectra of control samples suspended in TSB cultural medium (Fig. 4) can be attributed to the absorptions of amide I and amide II groups,32–34 indicating adsorption of protein‐like substances on the polymer surface, most likely coming from media, which contained proteins, lipids, and oligosaccharides. The extent of the proteins adsorption was maximized in OX‐PE, whereas it was barely detectable in the other PEs tested.…”
Section: Discussionmentioning
confidence: 99%
“…The ATR–FTIR bands in the spectra of control samples suspended in TSB cultural medium (Fig. 4) can be attributed to the absorptions of amide I and amide II groups,32–34 indicating adsorption of protein‐like substances on the polymer surface, most likely coming from media, which contained proteins, lipids, and oligosaccharides. The extent of the proteins adsorption was maximized in OX‐PE, whereas it was barely detectable in the other PEs tested.…”
Section: Discussionmentioning
confidence: 99%
“…In fact several investigations on the 45S5 Bioglass ® and other bioactive glasses have proved that the development of chemically stable crystal phases may sensibly reduce the reaction kinetics of bone tissue integration 35–37. Moreover, recent contributions have suggested that the crystallization may inhibit the protein adsorption and even promote inappropriate protein conformations for cell adhesion 38, 39…”
Section: Introductionmentioning
confidence: 99%
“…[34] Hence, we have performed the peak area analysis to demonstrate the effects of plasma power on the chemical composition of ppEtOz coatings. The Gaussian curve fitting process applied to amide I band (1 600-1 700 cm À1 ) to resolve the underlying bands of the ppEtOz coating spectrum (carrier gas flow rate was 5 sccm) which was obtained on coatings deposited at different effective plasma powers are reported in Figure 3a-d. A summary of the amide I band fit results is tabulated in Table 1.…”
mentioning
confidence: 99%